Enzymatic Studies of Isoflavonoids as Selective and Potent Inhibitors of Human Leukocyte 5-Lipo-Oxygenase - Sepulveda-Boza, S; Espinosa-Ferrada, V; Mascayano-Collado, C (Blackwell Publishing Ltd, 2015)
Continuing our search to find more potent and selective 5-LOX inhibitors, we present now the enzymatic evaluation of seventeen isoflavones (IR) and nine isoflavans (HIR), and their in vitro and in cellulo potency against human leukocyte 5-LOX. Of the 26 compounds tested, 10 isoflavones and 9 isoflavans possessed micromolar potency, but only three were selective against 5-LOX (IR-2, HIR-303, and HIR-309), with IC50 values at least 10 times lower than those of 12-LOX, 15-LOX-1, and 15-LOX-2. Of these three, IR-2 (6,7-dihydroxy-4-methoxy-isoflavone, known as texasin) was the most selective 5-LOX inhibitor, with over 80-fold potency difference compared with other isozymes; Steered Molecular Dynamics (SMD) studies supported these findings. The presence of the catechol group on ring A (6,7-dihydroxy versus 7,8-dihydroxy) correlated with their biological activity, but the reduction of ring C, converting the isoflavones to isoflavans, and the substituent positions on ring B did not affect their potency against 5-LOX. Two of the most potent/selective inhibitors (HIR-303 and HIR-309) were reductive inhibitors and were potent against 5-LOX in human whole blood, indicating that isoflavans can be potent and selective inhibitors against human leukocyte 5-LOX in vitro and in cellulo. Of the 26 compounds tested, 10 isoflavones and 9 isoflavans possessed micromolar potency, but only three were selective against 5-LOX (IR-2, HIR-303, and HIR-309), with IC50 values at least 10 times lower than those of 12-LOX, 15-LOX-1, and 15-LOX-2. Docking and steered molecular dynamics were performed to determinate the structure-activity relationship. © 2014 John Wiley & Sons A/S.